1990
DOI: 10.1121/1.399962
|View full text |Cite
|
Sign up to set email alerts
|

Observer efficiency and weights in a multiple observation task

Abstract: A sequence of seven tones, sampled from one of two distributions differing in mean frequency, is presented to observers who try to report which distribution was sampled. Estimates are obtained of the weight or importance given to each tone as a function of its temporal position. In five experiments, the reliability of the information is varied by changing the variance of the distributions; tones with high reliability are sampled from distributions with relatively small variance, whereas tones with low reliabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
78
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(84 citation statements)
references
References 14 publications
6
78
0
Order By: Relevance
“…We propose that the higher weight on segments with a higher mean level could be due to attention to the most physically intense elements. In fact, it has been reported that more intense elements receive higher weight even if they provide less information about the correct response than do less intense elements (Berg, 1990;Lutfi & Jesteadt, 2006;Turner & Berg, 2007) or, alternatively, and in many cases equivalently, that louder elements receive higher weight (e.g., . A potential explanation might be that more intense elements have a higher saliency than do less intense elements.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We propose that the higher weight on segments with a higher mean level could be due to attention to the most physically intense elements. In fact, it has been reported that more intense elements receive higher weight even if they provide less information about the correct response than do less intense elements (Berg, 1990;Lutfi & Jesteadt, 2006;Turner & Berg, 2007) or, alternatively, and in many cases equivalently, that louder elements receive higher weight (e.g., . A potential explanation might be that more intense elements have a higher saliency than do less intense elements.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the near-zero weights assigned to the fade-in segments mean that listeners did not make optimal use of the information available for classifying a given sound as either soft or loud (see Berg, 1990). As a consequence, was the accuracy in the absolute identification task inferior in the fade-in conditions?…”
Section: Sensitivitymentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, the components were the temporal segments constituting the level-fluctuating noise. If the participant assigns a large weight to a particular component-that is, if attention is directed to the component (Berg, 1990)-there will be a strong correlation between the component's random level perturbation and the participant's response. If on the other hand the component is unimportant for the decision, the responses will be statistically independent of the random variation (Kortekaas, Buus, & Florentine, 2003;Lutfi, 1995;Richards & Zhu, 1994).…”
mentioning
confidence: 99%
“…The effect of threshold microstructure (as measured by OAEs) on loudness perception is particularly noteworthy because relative loudness is also known to be one of the most important factors affecting the decision weights listeners place on different information-bearing components of sounds (Berg 1990;Lutfi and Jesteadt 2006;Epstein and Silva 2009;Thorson 2012;Rasetshwane et al 2013). This suggests that OAEs might be used to diagnose difficulty in target-in-noise listening tasks through their impact on decision weights.…”
Section: Introductionmentioning
confidence: 99%